Funcionamiento Diferencial DIF - -CEO-, Centro de Estudios de Opinión (La Sociología en sus Escenarios, 2010)
<!--[if gte mso 9]> Aigneren 12.00 <![endif]--><!--[if gte mso 9]> Normal 0 21 false false false ES-CO X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!-- /* Font Definitions */ @font-face {font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-1610611985 1107304683 0 0 415 0;} @font-face {font-family:Calibri; panose-1:2 15 5 2 2 2 4 3 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:-520092929 1073786111 9 0 415 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin-top:0cm; margin-right:0cm; margin-bottom:10.0pt; margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:Calibri; mso-fareast-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; mso-fareast-language:EN-US;} p.Default, li.Default, div.Default {mso-style-name:Default; mso-style-unhide:no; mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; mso-layout-grid-align:none; text-autospace:none; font-size:12.0pt; font-family:"Arial","sans-serif"; mso-fareast-font-family:Calibri; mso-fareast-theme-font:minor-latin; color:black; mso-fareast-language:EN-US;} .MsoChpDefault {mso-style-type:export-only; mso-default-props:yes; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:Calibri; mso-fareast-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; mso-fareast-language:EN-US;} .MsoPapDefault {mso-style-type:export-only; margin-bottom:10.0pt; line-height:115%;} @page WordSection1 {size:612.0pt 817.0pt; margin:97.0pt 41.75pt 32.85pt 58.05pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.WordSection1 {page:WordSection1;} --> <!--[if gte mso 10]> <![endif]--> Los tests o instrumentos de medida estandarizados se han convertido en una herramienta indispensable en las ciencias sociales, tales como la Psicología, la Sociología y la Educación. Por ello es primordial que los profesionales que los emplean se aseguren de que estos instrumentos funcionan del mismo modo en los distintos grupos existentes en función de variables socio-demográficas como el sexo, la cultura, la etnia, etc. Cuando alguno de los ítems funciona diferencialmente para los distintos grupos se habla de funcionamiento diferencial del ítem (DIF)1. Precisamente el objetivo del presente trabajo se centra en presentar una breve introducción al concepto de DIF y a los métodos existentes para su detección. Abstract Tests or standardized measuring instruments has become an indispensable tool in social sciences, such as Psychology, Sociology and the Education. For that reason he is fundamental that the professionals use who them assure that these instruments work in the same way in the different existing groups based on sociodemographic variables like sex, the culture, the ethnic group, etc. When some of the items diferencialmente works for the different groups operation speech differential of the item (DIF). Indeed the objective of the present work concentrates in presenting/displaying a brief introduction to the concept of DIF and the existing methods for its detection.